2015
DOI: 10.1111/dmcn.12786
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric manifestations of Sydenham's chorea: a systematic review

Abstract: OCDObsessive-compulsive disorder PANDAS Paediatric autoimmune neuropsychiatric disorders associated with streptococcal infections AIM Sydenham's chorea is a post-streptococcal, autoimmune, neuropsychiatric movement disorder. Sydenham's chorea is a major criterion for diagnosis of acute rheumatic fever with the implication of potential long-term sequelae including cardiac complications. It is well established that there is psychiatric comorbidity in Sydenham's chorea, but there are variations in the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 67 publications
4
44
0
Order By: Relevance
“…In rare instances the associated hypotonia can be so profound as to be completely disabling, a variant known as chorea paralytica or chorea mollis. Neuropsychiatric symptoms, including obsessive compulsive behaviors, personality changes, emotional lability, distractibility, irritability, anxiety, age-regressed behaviors, and anorexia, are common and frequently predate the appearance of chorea 1. After improvement of their motor symptoms, many patients with SC continue to have a high rate of anxiety and depression2 as well as difficulty with cognitive tasks requiring attention and processing speed 3.…”
Section: Introductionmentioning
confidence: 99%
“…In rare instances the associated hypotonia can be so profound as to be completely disabling, a variant known as chorea paralytica or chorea mollis. Neuropsychiatric symptoms, including obsessive compulsive behaviors, personality changes, emotional lability, distractibility, irritability, anxiety, age-regressed behaviors, and anorexia, are common and frequently predate the appearance of chorea 1. After improvement of their motor symptoms, many patients with SC continue to have a high rate of anxiety and depression2 as well as difficulty with cognitive tasks requiring attention and processing speed 3.…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that Sydenham's chorea is commonly associated with psychiatric symptoms, including obsessive-compulsive disorder, tic disorders and ADHD [12]. Antibodies against group A beta-hemolytic streptococcus which cross-react with basal ganglia have been demonstrated as the etiology [13].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against group A beta-hemolytic streptococcus which cross-react with basal ganglia have been demonstrated as the etiology [13]. The available literature indicates that the treatment of psychiatric disorders is challenging due to the high risk of motor-related side effects of psychotropic medications [12,14]. One earlier study found a high frequency of adverse reactions to central stimulants and suggested that Sydenham's chorea in childhood leads to a sensitivity to agents that augment central dopaminergic activity, which may be expressed as acute chorea [15].…”
Section: Discussionmentioning
confidence: 99%
“…Punukollu et al . report a systematic review on the neuropsychiatric manifestations of Sydenham's chorea.…”
mentioning
confidence: 99%
“…Based on the significant evidence of behavioral and cognitive symptoms in patients with Sydenham's chorea, Punukollu et al . argue the need for early recognition of these symptoms and their multidisciplinary management.…”
mentioning
confidence: 99%